ISLAMIC RELIGIOUS EDUCATION LEARNING MODEL WITHIN THE FRAMEWORK OF THE INDEPENDENT CURRICULUM - Siti Hartutik; Khozin Khozin; Rahmad Hakim (El Midad, 2025)
This study aims to describe the application of the Islamic Religious Education (PAI) learning model based on the Independent Curriculum in Aisyiyah 11 Musi Rawas Kindergarten, South Sumatra. The Independent Curriculum is a new policy in the Indonesian education system that provides freedom for educators to design learning that suits the needs and potential of students. At the Kindergarten (TK) level, the implementation of the Independent Curriculum is expected to foster character, faith, and devotion in children from an early age through a fun approach and activating children's participation. This study uses a qualitative descriptive method with a case study approach to explore how the PAI learning model is in accordance with the principles of the Independent Curriculum applied in Aisyiyah 11 Kindergarten. Data was collected through observations, interviews, and documentation involving teachers, principals, and parents. The results of the study show that the implementation of the Independent Curriculum-based PAI learning model at Aisyiyah 11 Musi Rawas Kindergarten refers to the Play-Based Learning Model with the principles of the Independent Curriculum which is more flexible and focuses on developing students' potential. Learning is carried out with a fun approach and is based on the needs and interests of children, and provides room for creativity. Teachers use story, game, and theme-based methods to instill Islamic religious values in children.